Application of The Exponential Smoothing Method in Predicting The Visit of Foreign Tourists to Indonesia - Rusdiana, Siti; Rahayu, Latifah; Asmanidar, Asmanidar (Syiah Kuala University, 2022)
Indonesia is rich in natural beauty, diverse ethnic groups, cuisines, and languages, making it one of the most popular destinations for both domestic and international tourists. The purpose of this study is to forecast the number of foreign tourist visitors from 2020 to 2021. The government can improve facilities or infrastructure while also preserving the beauty and culture of Indonesia's various ethnic groups. This study will investigate 101 foreign countries that visited Indonesia using one of the Exponential Smoothing methods. In forecasting, the Triple Exponential Smoothing method has three smoothing times. Forecasting in 101 foreign tourists visiting Indonesia yields different parameter results because each result has a different smoothing value. Once the parameters ranging from 0.1 to 0.9 is close to forecasting results, there are close to the actual value. The search ends at one of these parameters because it already yields the expected results to calculate the error value using the MAPE method. There were 20 foreign tourists selected based on the average number of visits to Indonesia.